Kebijakan Hukum Pidana dalam Upaya Penanggulangan Tindak Pidana Lingkungan Hidup dalam Undang-undang Cipta Kerja: Kebijakan Hukum Pidana dalam Upaya Penanggulangan Tindak Pidana Lingkungan Hidup dalam Undang-undang Cipta Kerja - Jiwanti, Ainun (JUSTISI, 2023)
This study aims to analyze how criminal law policies in dealing with environmental crimes in Law Number 6 of 2023 concerning Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation to Become a Law (“Law concerning Determination of Job Creation GRL to Become a Law”). This research uses normative legal research or doctrinal legal research. The approach used is the statutory approach, as well as the technique of tracing legal materials by means of a literature study. The results showed that in the Law concerning Determination of Job Creation GRL to Become a Law there was a political shift in environmental law enforcement law, namely there was a change in the types of sanctions for several actions that were previously threatened with criminal sanctions in the Environmental Protection and Management Law (Law No. 32/2009) but in the Law concerning Determination of Job Creation GRL to Become a Law they were threatened with administrative sanctions. The Law concerning Determination of Job Creation GRL to Become a Law also has not accommodated a number of important regulations, namely relating to the system for formulating criminal penalties, where there is no minimum penalty limit, criminal provisions in lieu of fines that are not paid by corporations and the obligation to impose sanctions for environmental improvement measures. Therefore, the Law concerning Determination of Job Creation GRL to Become a Law needs to be revoked or revised before it is enacted into law in order to realize environmental-oriented law enforcement. Keywords: Criminal law policy; Environmental Crime; Job Creation Law.